Analysis of stomach content of piscivorous fishes caught in Danau Panggang Peatland, South Kalimantan, Indonesia - Dini Sofarini; ENDANG YULI HERAWATI; MOHAMMAD MAHMUDI; ASUS MAIZAR SURYANTO HERTIKA; DIANA ARFIATI; MUHAMMAD MUSA; MOHAMAD AMIN; SUPRIHARYONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sofarini D, Herawati EY, Mahmudi M, Hertika AMS, Arfiati D, Musa M, Amin M, Supriharyono. 2019. Analysis of stomach content of piscivorous fishes caught in Danau Panggang Peatland, South Kalimantan, Indonesia. Biodiversitas 20: 3788-3793. The purpose of this study was to analyze the stomach content profile of piscivorous fishes caught at the reservaat station and the station without activity as The control station, in the Danau Panggang peatland. Sampling was carried out four times and the index of preponderance stomach content was determined in piscivorous fishes. The results showed there were nine fish species in the reservaat area, including Cryptopterus spp., Pangasius nieuwenhuisii, Chana striata, Anabas testudineus, Pangasius sp., Mastecembelus erythrotaenia, Macrognathus aculeatus, Mystus nigriceps, and Mystus nemurus. Their gut was dominated 89% by Chrysophyta, and 37.5% by Diatom and Navicula. In the area without activity, six species of fish were caught, including Cryptopterus spp, Pangasius nieuwenhuisii, Anabas testudineus, Pangasius sp, Mystus nigriceps, and Mystus nemurus, with 83% of their gut dominated by Diatom. The water temperature was 28.07-33.25º C, brightness (6-115 cm), pH of 4.23-6.97, dissolved oxygen (DO) (1.4-6.5 mg/L) and BOD (7.52-24.92 mg/L) i.e., water quality parameters that tend to be incompatible with the persistence of fishes. These limiting factors of peatland water and extreme conditions led to a limitation at availability of natural food for piscivorous fishes.